Some (p-MeOC6H4) (p-Me2NC6H4)Te and (p-EtOC6H4) (p-Me2NC6H4)Te Molecular Adducts with Monodentate Ligands - Srivastava, Shekhar; S. Gupta, Hari; Gautam, Deepa (Asian Journal of Chemistry, 2012)
Twenty molecular adducts of (p-MeOC6H4) (p-Me2NC6H4)Te and (p-EtOC6H4) (p-Me2NC6H4)Te with various monodentate ligands of the type RR'Te.L have been synthesized and analysed to assign their structure by elemental analysis, molar conductivity, IR and X-ray photoelectron spectroscopy.